ANALYSIS OF DA'I COMMUNICATION SKILLS TOWARDS THE MUSLIM CONVERTED KAROMBA COMMUNITY - Arianto Arianto (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2021)
Da'wa communication skills are needed in preaching to the converts community because the conditions of converts are different from those of Muslims in general. The success of this da'wa can be achieved if converts as the target of preaching carry out the da'wa message conveyed by the preacher. The research objective was to map the preachers' da'wa communication skills to the converts in Karomba, Pinrang district. This study used a qualitative approach and case study methods, so the primary data were in-depth interviews and observations. In addition, this study uses inductive data analysis. The study results indicate that the preachers apply three da'wa communication skills to the converted Muslim community to support da'wa's success. First, the skills to produce messages, especially messages of faith and morals. Second, the skills to receive and convey messages, mainly using local languages. Third, the skills to interact with the converts community through sharia consultation activities. This research is necessary because the findings of this study can serve as a guide for preachers to increase preaching success, especially preaching to converts.